Prevalência de marcadores sorológicos dos vírus das Hepatites B (VHB) e C (VHC) em indivíduos infectados por Schistosoma mansoni no bairro Santa Maria, Aracaju/SE - Santos, Márcio Bezerra (2012)
The Schistosomiasis is a parasitic disease, severe, chronic waterborne and development, whose etiologic agent is Schistosoma mansoni. It occurs in 74 countries with 207 million people infected and 700 million in risky areas. In Brazil, data indicate a prevalence of eight million. The Schistosomiasis can be exacerbated when patients are carriers of the Hepatitis B Virus (HBV) and C (HCV), resulting in simultaneous evolution of both pathologies. In Brazil, the prevalence of co-infection with HBV/HCV and S. mansoni found in studies ranged from 13.6% to 40% for HBV and 0.5% to 19.66% for the HCV. On this basis, this research aimed to identify the prevalence of serological markers of HBV and HCV and risky factors in individuals carrying the S. mansoni in the Santa Maria neighborhood, Aracaju, state of Sergipe. We conducted a cross-sectional epidemiological study. Data were collected for each patient by means of a questionnaire investigation. This questionnaire included variables identifying the subject of the research participants and variables that included the epidemiological risky factors for infection with HBV or HCV. We collected serum samples of research participants and forwarded to the laboratory testing to identify serological markers of hepatitis B and C: Total Anti-HBc IgG, Anti-HBs, HBsAg and Anti-HCV. All procedures performed using the technique of chemiluminescence immunoassay using the ARCHITECT assay for each serological marker following the protocols established by the laboratory equipment manufacturer SYSTEM ARCHITECT. In addition, we carried out the analysis of spatial distribution of co-infection in the district through the program using the TerraView Kernel intensity estimation. It was found that 16 individuals had contact with HBV (9.41%), one of these was positive for HBsAg. Only Thirty-two samples (18.82%) were positive for the marker Anti-HBs. Three samples were positive for anti-HCV (1.76%), and also a positive for Anti-HBc. The main risks of HBV and HCV infection were related to parenteral interventions of health services, as well as sexual activity without condom use in the case of HBV. Spatial analysis of cases of co-infection (Schistosomiasis and Hepatitis) allowed the visualization of areas of higher concentration of these infections, as well as those that are exposed to different degrees of risk of transmission. The survey results allow to offer, the municipal health services, a tool to facilitate the understanding of the spatial distribution of schistosomiasis and hepatitis (B and C) in Santa Maria neighborhood. Although our values are above the estimated prevalence for the Brazilian population and the Northeast, we can t infer that the individuals with Schistosomiasis are more susceptible to infection with HBV or HCV, since the risky factors were the means of risky transmission of causative agents of hepatitis and not infected with S. mansoni.